Effect of Kangaroo Mother Care on the Psychological Stress Response and Sleep Quality of Mothers With Premature Infants in the Neonatal Intensive Care Unit - Chen, Wei-yan; Wu, Ying-ying; Xu, Meng-yan; Tung, Tao-Hsin (Frontiers in Pediatrics, 2022)
Objective:To investigate the effect of kangaroo mother care on the psychological stress response and sleep quality of mothers with premature infants admitted to the neonatal intensive care unit (NICU). Methods: The study recruited 132 mothers of premature infants from the NICU of our hospital from January 2019 to January 2020. The participants were divided into the experimental and control groups according to the random number table method (66 mothers per group). The control group was managed with conventional premature infant treatment, nursing programmes, and discharge education, whereas the experimental group was managed with a 4-week kangaroo mother care intervention. The psychological stress state and sleep status of mothers with preterm infants in both the groups were evaluated using the Symptom Check List 90 (SCL-90) and Assens Insomnia Scale (AIS). Results: After the intervention, the total SCL-90 score and factor scores, such as coercion, interpersonal relationships, depression, anxiety, hostility, and additional factors, were lower in the experimental group than in the control group (P<0.05). The total AIS score and factor scores of night waking, earlier waking, total sleep time, total sleep quality, daytime mood, daytime body function, and daytime sleepiness were lower in the experimental group than in the control group (P<0.05). Conclusions: The Kangaroo mother care approach can relieve adverse psychological stress and improve the sleep status of mothers of NICU premature infants after mother-infant separation. It can be promoted and used in mothers of premature infants in the NICU to enhance physical and mental health.